Virtual learning environment for managing costs of dressings for pressure ulcers - Marta Cristiane Alves Pereira; Yolanda Dora Martinez Évora; Rosângela Andrade Aukar de Camargo; Carla Regina de Souza Teixeira; Amanda Cristiny Andrade Cruz; Helena Ciavatta (Universidade Federal de Goias, 2014)
A descriptive and applied study aimed at describing the construction and assessment of a virtual learning environment on the topic of cost management of pressure ulcer dressings, using WebQuest methodology. For the planning and development phases, we used simple and accessible technological resources, focused on educational aspects. During the assessment phase, four computer science specialists, four nursing professors and four nursing professionals who worked with cost management evaluated technical aspects (Response Time and Interface Quality) as well as educational ones (Content, Activity, Interaction). These aspects received positive evaluations (over 86% of criteria were fulfilled), except for Response Time (62% were totally fulfilled and 30% partially fulfilled). The results demonstrated that it is possible to make use of virtual learning environments with undergraduate nursing students in order to impact education regarding material cost management in nursing. doi: 10.5216/ree.v16i2.22161.